The Road Safety Advocates of the Philippines (RSAP): A 10- Year Assessment And Strategic Roadmap for the Next Decade (International Journal of Environmental Sciences, 2025)
This study explores the effectiveness of the Road Safety Advocates of the Philippines (RSAP), a non-governmental organization (NGO) championing road safety in the Philippines. Employing a mixed-method approach, the research combines a survey targeting RSAP's followers and an internal analysis of the organization itself.The study investigates the demographics of RSAP's base, their assessment of the organization's performance, and desired future directions. Survey findings reveal a male-dominated (78%) membership base concentrated in the 35-44 age group. Nearly half (46%)of respondents held college degrees. The majority(69%) are employed, which primarily (36%) comes from the food businesses and private institutions. Social media is the primary engagement platform, with high satisfaction expressed towards RSAP's services. RSAP is viewed to have strong leadership, a social media presence, and a robust supporter database. Opportunities include services tailored for women riders, harnessing political power, and establishing a Road Safety Academy. Potential threats encompass limited staff and volunteer training, and competition from other motorist-oriented parties.The study concludes that RSAP plays a significant role in motorcycle riders’ and motorists’ safety. By addressing its weaknesses and capitalizing on its strengths and opportunities, particularly through formalization, informative publications, and engagingwomen, RSAP can solidify its leadership position. Fostering collaboration with law enforcement and effectively responding to competition iscrucial for long-term success. This research contributes academically to the understanding of advocacy group effectiveness in the Philippines and offers practical insights for RSAP to enhance its performance and impact.